General Use of Chinese Herbal Products among Female Patients with Mastitis in Taiwan. (25th March 2022) - Chou, Shu-Huey; Huang, Chun-Che; Lin, Ching-Heng; Wu, Kun-Chang; Chiang, Pei-Jung
Abstract : Objectives . Little information is available regarding the use of Chinese herbal medicine to treat mastitis. This study evaluated the prescription patterns of Chinese herbal medicine products in women with mastitis in Taiwan. Design . This is a population-based cross-sectional study. Setting . 8, 531 women aged 20–49 years, who received a diagnosis of mastitis between 2004 and 2013, were identified from the Longitudinal Health Insurance Database in Taiwan. We collected data on demographic characteristics, including age, monthly insurance premium, and urbanization level. The ten most Chinese herbal medicines prescribed for mastitis were assessed, including frequency, percentage, average daily dose, and average duration of prescription. Main outcome measures . We analysed the ten most single Chinese herbs and Chinese herbal formulae prescribed for mastitis. Results . Overall, 437 (5.1%) women received Chinese herbal medicine to treat mastitis. Mai Men Dong ( Ophiopogon japonicus (Thunb.) Ker Gawl.; 22.3%), Pu Gong Yin ( Taraxacum mongolicum Hand.-Mazz.; 7.8%), and Wang Bu Liu Xing ( Vaccaria hispanica (Mill.) Rauschert; 3.5%) were three of the most commonly prescribed single Chinese herbs for mastitis. Xian-Fang-Huo-Ming-Yin (18.2%), Jia-Wei-Xiao-Yao-San (9.1%), and Chai-Hu-Shu-Gan-San (8.4%) were three of the most commonly prescribed Chinese herbal formulae. Conclusion . Xian-Fang-Huo-Ming-Yin can clear heat, detoxify body, alleviate swelling, activate blood, and relieve pain. It was the most frequently prescribed Chinese herbal formula in patients with mastitis.